Invisible strings - Siegel Carlson, Barbara (Primerjalna književnost, 2019)
The epigraph in poet Jean Valentine's book Break the Glass: "A pencil/for a wing bone" (by Lorine Neidecker) leads us to consider the way writing allows for transcendence. Similarly, in her work, Meta Kušar brushes out stars with a comb and then finds "an accomplice/combed/in this hollowed-out place". From the two countries US and Slovenia of such vastly different sizes, these poets, both influenced by such luminaries as Emily Dickinson and Marina Tsvetaeva, have carved out intimate spiritually enriching spaces where consciousness meets the sublime. Focusing on Kušar's view of Heraclitus as a teacher who "understood invisible strings are stronger than visible ones," I will explore the thematic, literary and stylistic connections between these two literary stars, as well as some of their differences in how they cultivate a poetics of the invisible that illuminates the mysterious underworld of the human soul as it negotiates the political, philosophical and ethical realms of contemporary existence.
Keywords: ameriška poezija; feminizem; književnost; Kušar, Meta; poetika nevidnega; primerjalne študije; slovenska poezija; Valentine, Jean